Apparently there were complaints : a memoir - Gless, Sharon (Simon & Schuster, 2021)
"APPARENTLY THERE WERE COMPLAINTS is both a deeply personal story about Gless's complicated family and her struggles with alcoholism and fear of romantic commitment and a juicy, hilarious tell-all about Hollywood and Sharon's encounters with some of the industry's biggest stars. Gless puts it all out on the page in the same way she has lived--never with moderation"--